Factors influencing the confidence in core clinical skills among hospital nurses. Issue 6 (8th April 2014) - Yang, Young Ok; Kim, Minju; Park, Kyung‐Yeon; Yang, Jin‐Hyang
Abstract : The purpose of this study was to examine the confidence to perform 20 clinical skills and identify factors influencing the confidence of hospital nurses. A descriptive, cross‐sectional study was conducted with 550 hospital nurses at four hospitals in B city, Korea. The confidence to perform, frequency of performance and educational needs on 20 clinical skills identified by Korean Accreditation Board of Nursing were measured with a self‐reported questionnaire. Data were analysed by SPSS 19.0 (IBM Corporation, Armonk, New York, USA). Participants were 27 years old on average, and 49.5% had less than 3 years of total working experience. The most confident skill was measuring vital signs, whereas the least confident skill was using defibrillator. In results of stepwise regression, confidence to perform was associated with educational needs, total working experience, frequency of performance and position. It is necessary to give opportunities to practice clinical skills at both schools and clinics for producing well‐prepared nurses.